Pereskia bleo leaves extract induces cell death via cell cycle arrest and apoptosis in cervical cancer cells hela - Salleh, Siti Farhanah Mohd; Ibrahim, Wan Suriyani Wan; Ismail, Norzila (Taylor & Francis (Routledge), 2019)
Introduction: Pereskia bleo is a leafy and edible plant, locally known as “Pokok Jarum Tujuh Bilah” which has anticancer properties. This study purposed to determine the cytotoxic effects of P. bleo leaves extracts on several well-known cancer cells and elucidate its underlying mechanism in inducing cell death. Methods: Cytotoxic activity on selected cell lines was determined using MTT assay. Mechanism of cell death was investigated through cell cycle and Annexin V assay. Expression of apoptotic proteins was measured by flow cytometry method. Results: Ethyl acetate extract of P. bleo leaves (PBEA) appeared to have the strongest IC50 value (14.37 ± 8.40 lg/ml) and most active against HeLa cells was further studied for apoptosis. The cell cycle investigation by flow cytometry evidenced the increment of PBEA treated HeLa cells in G0/G1 phase and apoptotic event was detected in Annexin V assay. Analysis of apoptotic protein showed pro-apoptotic proteins (Bax, p53 and caspase 3) were triggered where as anti-apoptotic protein Bcl-2 was suppressed in treated HeLa cells. Conclusions: Our findings demonstrated that PBEA treatment induced cell death in HeLa cells by p53-mediated mechanism through arresting cell cycle at G0/G1 phase and mitochondrial-mediated pathway with involvement of pro-apoptotic proteins, anti-apoptotic protein, and caspase 3.